Results of Cement with Screw Augmentation for Large Tibial Defects in Primary TKA - Techapaitoon, Wasu (Journal of Southeast Asian Orthopaedics, 2021)
Objectives: To compare the outcome of TKAs using screw augmentation and cement in cases involving a large tibial defect with conventional TKA procedures in cases with no tibial defect using clinical and radiographic data. Materials and Methods: A retrospectively reviewed of 217 TKAs that operated at Nakhon Pathom Hospital from January 2010 - March 2021.TKAs have divided into 54 knees with a large tibial defect treated using screws with cement augmentation (the screws group), and 163 knees with a small or no tibial defect treated with conventional TKA procedures (the no screws group). Patient information collected included age, gender, limb alignment, length of follow-up period, defect depth, presence of radiolucency lines, Knee Society scores and incidence of prosthesis loosening. Results: There was no statistically significant differences between the groups in mean ages (64 yrs.), follow-up period (6 yrs.), BMI, gender (female 88%) and post-operative overall alignment (4.35o). While pre-operative varus angle of screw group (-15.96o), incidence of radiolucency lines of screw group (59%) and improvement of Knee Society Scores after surgery were significantly differences (P-value < 0.001). The average defect depth was 11.99 mm and most of the depths was in range of 10-20 mm. There were 6 cases of loosening prosthesis in the no screws group and 3 cases in the screws group. The survival rate of implants was 96% in the no screws group and 94% in the screws group with no difference in statistic. Conclusions: At mean follow-up of 6 years, the cement with screw augmentation for large tibial defects had a survival rate equal to conventional TKA in cases without bone defect and had a lower cost than metal augmentation. This technique is recommended for defect depths of between 6-20 mm.